The Extent of Derivative Usage by Large Non-Financial Firms in Europe - Rodrigues Da Costa, Victoria (2009)
Following on from previous empirical work, this study examines firm’s intensity decision in their use of derivative instruments and provides empirical evidence from a sample of 206 non-financial firms listed on the FTSEurofirst 300 Index, across eight business sectors and sixteen European countries. The results of the Multiple Regression analysis provide evidence to support some of the theoretical predictions laid out in the literature. In particular, it finds leverage and firm size significant at the 1% level. Moreover, it also finds the price to earnings ratio to be significant at the 10% level, and consumer services and telecommunications to have statistically lower derivative usage than utilities firms. However, this study finds interest cover, preference stock, convertible bonds, liquidity, dividend payout ratio, price to book and country to be insignificant.